2023
DOI: 10.1021/jacs.2c11395
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Rate Determines the Blinking Propensity of Rhodamine Fluorophores for Super-Resolution Imaging

Abstract: Live-cell single-molecule localization microscopy has advanced with the development of self-blinking rhodamines. A pK cycling of <6 is recognized as the criterion for self-blinking, yet a few rhodamines matching the standard fail for superresolution reconstruction. To resolve this controversy, we constructed two classic rhodamines (pK cycling < 6) and four sulfonamide rhodamines with three exhibited exceptional larger pK cycling characteristics (6.91−7.34). A kinetic study uncovered slow equilibrium rates, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Owing to the reversible process of the rhodamine switch ring and the excellent contrast of light and dark, it can be positioned multiple times in the imaging, improving the positioning density and positioning accuracy of the imaging. 123–128 Therefore, rhodamine dyes are widely used in super-resolution imaging research.…”
Section: Rhodamine Derivatives For Bioimagingmentioning
confidence: 99%
“…Owing to the reversible process of the rhodamine switch ring and the excellent contrast of light and dark, it can be positioned multiple times in the imaging, improving the positioning density and positioning accuracy of the imaging. 123–128 Therefore, rhodamine dyes are widely used in super-resolution imaging research.…”
Section: Rhodamine Derivatives For Bioimagingmentioning
confidence: 99%
“…However, we found that such constructs suffered from poor reactivity of the Tz moiety and were susceptible to hydrolytic cleavage of the Tz unit. In our second strategy, we constructed a PaX (S9, see Supporting Information) with an acrylate moiety as the linker/radical trap, which served to generate a series of the dyads bearing either secondary (9,10) or tertiary (11,12) acrylamide linkages. Initial TD-DFT studies 28 anticipated excited state energy transfer to the Tz moiety in both the singlet and triplet manifolds for the PaX structures, regardless of linkage (Figure S1a), as well as quenching of the singlet excited state of the photogenerated (i.e., "closed-form") pyronine fluorophore (PaX CF , Figure 1b and Figure S1b).…”
Section: Synthesis and Characterization Of Pax Tetrazinementioning
confidence: 99%
“…To prepare the acrylamide-linked PaX scaffolds (9−12), new acrylate-functionalized PaX were prepared (S9, see Supporting Information for details) and coupled to commercially available tetrazine amines to yield the secondary acrylamide products (9,10). To access the tertiary Nmethylacrylamides (11,12), N-methyl-4-(6-methyl-1,2,4,5tetrazin-3-yl)benzylamine 41 was additionally synthesized and coupled with the acrylic acids S9 and S14 (see Supporting Information). Much to our surprise, the acrylamide-derived PaX scaffolds showed notably slower photoactivation rates, likely due to the greater electron deficiency of the radical trap.…”
Section: Synthesis and Characterization Of Pax Tetrazinementioning
confidence: 99%
See 1 more Smart Citation
“…48 Moreover, multi-color imaging in dSTORM is often challenging and requires careful consideration and optimization of dyes. 49,50 Therefore, matching an appropriate fluorophore and buffer system is crucial in PDMS-based devices. By trapping the fluorophores in the fluid pockets of oxidized PDMS (see ESI † for detailed information), we were able to recreate similar environment experienced by immobilized chromatin in closed nanochannels for dSTORM dye optimization.…”
Section: Optimal Dstorm Dye Combination For H-pdms Systemmentioning
confidence: 99%